Primary Healthcare in Saudi Arabia: An Evaluation of Emergent Health Trends - Angela Caswell; Joyce Kenkre (Global Journal on Quality and Safety in Healthcare, 2021)
Introduction: The Kingdom of Saudi Arabia (KSA) is experiencing an increasing demand for healthcare due to a growing population and unhealthy changes in lifestyle, fostering the need for critical examination of the current status of primary healthcare in the KSA with analysis of health-related trends among its growing population. Methods: A review of the literature was therefore undertaken, followed by a survey of primary healthcare centers at three facilities in Riyadh, to assess the current activities, understand challenges, compare existing practices with international best practices, and asses the level of patient satisfaction. The level of satisfaction with primary care services was examined by using observational surveys and retrospective reviews from the previous 20 years. Results: The more rural areas with populations with lower education and income ranked factors such as cleanliness, competence of staff, and environment the highest (82–95%), whereas urban areas with populations with higher education and income rated their level of satisfaction lower (74–82%). The influence of population diversity and the country's unique cultural sensitivities on the awareness and uptake of cancer surveillance services available in the community was examined. The incidence of diabetes, asthma, obesity, along with breast and cervical cancer trends, has illustrated the importance of health education and disease prevention. Conclusion: An investment in resources for primary healthcare staff and medical facilities is strongly recommended to support primary care providers in becoming the accepted and preferred community frontline for healthcare needs’ assessment and care delivery. With its nursing staff comprised predominantly of expatriates, the emphasis needs to be on recruitment and training of a Saudi national workforce in line with succession planning strategy toward a sustainable Saudi workforce.